Development and Validation of Stability-indicating RP-HPLC Method for Estimation of Pamabrom in Tablets - Shah, U. (Medknow Publications & Media Pvt Ltd, 2014)
The present study depicts the development of a validated RP-HPLC method for the determination of the pamabrom in presence of degradation products or other pharmaceutical excipients. Stress study was performed on pamabrom and it was found that it degrade sufficiently in acidic, alkali and oxidative condition but less degradation was found in thermal and photolytic condition. The separation was carried out on Enable G 120 A(0) (250×4.6 mm, 5 μ) column having particle size 5 μ using methanol: water (75:25 v/v) with pH 4.0 adjusted with ortho phosphoric acid as mobile phase at flow rate of 1 ml/min. The wavelength of the detection was 280nm. A retention time (R(t)) nearly 3.9 min was observed. The calibration curve for pamabrom was linear (r(2) = 0.9997) from range of 10-60 μg/ml with limit of detection and limit of quantification of 1.41 μg/ml and 4.28 μg/ml, respectively. Analytical validation parameter such as selectivity, specificity, linearity, accuracy and precision were evaluated and relative standard deviation value for all the key parameters were less than 2.0%. The recovery of the drug after standard addition was found to be 101.35%. Thus, the developed RP-HPLC method was found to be suitable for the determination of pamabrom in bulk as well as stability samples of tablets containing various excipients.